2011
DOI: 10.1007/s13197-011-0373-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure blanching on sensory and proximate composition of peanut milk

Abstract: Small scale process for the production of peanut milk was developed from M-522 variety of peanut. Three treatments i.e. traditional, 1% NaHCO3 soaking and pressure blanching (at 121 °C, 15 psi for 2, 3 and 5 mins) were given for the preparation of peanut milk. The milks so obtained were analyzed for chemical composition and also subjected to organoleptic evaluation using nine point hedonic scale by semi trained panel of judges. Peanut milk prepared by pressure blanching (at 121 °C, 15 psi for 3 min) was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…Jain et al . () reported changes in proximate composition parameters due to pressure blanching in peanut milk samples. The authors reported that pressure blanching caused decrease in protein content which was probably due to structural changes and denaturation of proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jain et al . () reported changes in proximate composition parameters due to pressure blanching in peanut milk samples. The authors reported that pressure blanching caused decrease in protein content which was probably due to structural changes and denaturation of proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Peanut is the major oilseed crop of India accounting for more than 55% of oilseed production (Jain et al ., ). Peanut and its products are also well‐known for their nutritional benefits for young and old people because of their richness in terms of protein, minerals, essential amino acids as well as essential fatty acids such as linoleic and oleic acids which are considered to be highly valuable for human nutrition.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Peanut beverage is easy to prepare and its amino acid composition meets people's nutritional requirement (Howard, Hung, & McWatters, 2010;Jain, Yadav, Rajput, & Bhatt, 2013). Therefore, it has great potential as a dairy substitute or supplement.…”
Section: Introductionmentioning
confidence: 99%
“…The hedonic scale has been used in acceptability studies of diverse products (Cardoso et al 2013;Jain et al 2013;Kremer et al 2013), as well as for sensory psychophysical and intercultural studies (Nicolas et al 2010;Chung and Han 2013;Menichelli et al 2013).…”
Section: Introductionmentioning
confidence: 99%